China's regional CO2 emissions reduction potential: A study of Chongqing city. (15th January 2016) - Tan, Xianchun; Dong, Lele; Chen, Dexue; Gu, Baihe; Zeng, Yuan
Highlights: A three-phase model of regional CO2 emission reduction potential was built. Chongqing, the only municipality in the Midwest of China, was taken as example. The driving factors of CO2 emission in Chongqing were analysed. The future CO2 emission reduction potential in Chongqing was predicted. The difficulties of achieving CO2 emission reduction targets in 2020 were assessed. Abstract: Since China has put forward a series of obligatory Greenhouse Gas (GHG) emission reduction targets, provincial governments have issued provincial-level "Twelfth Five-Year" carbon intensity (CO2 emissions/GDP) reduction targets. There are 653 cities distributed throughout the eastern, middle and western parts of China, and each region has different quotas and paths to reduce GHG emissions, while the western part has greater challenges than the others. This paper predicts CO2 emission reduction potential of Chongqing, assesses the difficulty of achieving its CO2 emission reduction targets, and analyses its low-carbon transition path. The results show that the carbon intensity of Chongqing in 2020 will range from 1.58 to 1.75 ton CO2 /10 4 RMB, and there exist some scenarios with strong potential to meet carbon intensity reduction targets for 2020. Improved technology, energy efficiency, the optimization of energy input mix, and the adjustment of industrial structure are suggested to be major strategies to reach Chongqing's carbon intensity targets.